Effect of irrigation with magnetized and ionized water on yield, nutrient uptake and water-use efficiency of winter wheat in Xinjiang, China - Xinyue Chen; Kai Zhang; Xiaopeng Gao; Xin Ai; Guoyue Chen; Xiaomeng Guo; Chengcheng Wu; Lu Zhang (Agricultural Water Management)
Magnetization can alter hydrogen bonds among water molecules, leading to changes in water physicochemical properties, and ionization can use frequencies to break down polymers for better solubility. Consequently, irrigating with magnetized and ionized (MI) water might affect crop growth, yield, and water-use efficiency. This study investigated the effects and mechanisms of irrigation with MI water on water physicochemical properties, soil nutrient availability, winter wheat growth, nutrient uptake, yield, and water-use efficiency in Xinjiang, an arid region of northwest China. Our results showed that magnetization and ionization significantly increased water-dissolved oxygen and reduced water surface tension. Irrigation with MI water significantly increased soil available nitrogen and phosphorus concentrations at the heading and ripening stages. Additionally, irrigation with MI water significantly increased plant height, stem diameter, head length, and wheat biomass at the filling stage. Irrigation with MI water also enhanced wheat phosphorus uptake and grain yield, resulting in a 23 % improvement in water-use efficiency. In conclusion, irrigation with MI water can improve soil nutrient availability, stimulate wheat growth, and increase both grain yield and water-use efficiency, which could be applied in the fields of arid regions to enhance water use efficiency and sustainable agricultural water management.